Recycling of multilayer polymer packaging doypack - Borysovska, O.; Bovsunovsky, V. (Видавництво НТУ "ДП", 2022)
The purpose of this work is to study the range of polymer multilayer composite packaging doypack in retail chains and finding possible ways to solve the problem of its recycling. Methodology. Research on the range of polymer multilayer doypack packaging in Dnipro retail chains was conducted by selecting 20 different groups of goods in the three largest retail chains in Dnipro – ATB, Silpo and Varus. The composition of the combined package was determined by studying the appropriate labelling. Investigations of the properties of the crushed polymer multilayer doypack packaging were carried out using a microscope.
Утилізація багатошарової полімерної упаковки дой-пак
Keywords: waste; multi-layered combined doypack packaging; recycling; environmental pollution; extended producer responsibility; відходи; багатошарова комбінована упаковка дой-пак; вторинна переробка; забруднення довкілля; розширена відповідальність виробника